2018
DOI: 10.2514/1.b36435
|View full text |Cite
|
Sign up to set email alerts
|

Electric Field Damping of Rijke Tube Combustion Instabilities

Abstract: A direct-current electric field was investigated as a damping method for thermoacoustic instabilities generated in a horizontal Rijke tube driven by a premixed propane torch. Electrode lengths of 2.54, 5.08, and 15.24 cm were used with electrode locations relative to the burner tip of −4.60, −2.06, and 0.458 cm and voltages up to 4.68 kV being tested. Electrodes downstream of the burner tip, rather than surrounding the burner, and longer electrodes were most effective at damping instabilities. Damping also inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In Henderson and Xu [35] , the effect of a DC field on a Bunsen style flame inside of a Rijke tube was studied. The authors found the application of a DC voltage suppressed the instability amplitude, reaching a maximum suppression of 21 dBA.…”
Section: Electric Fields Applied To Thermoacoustic Instabilitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In Henderson and Xu [35] , the effect of a DC field on a Bunsen style flame inside of a Rijke tube was studied. The authors found the application of a DC voltage suppressed the instability amplitude, reaching a maximum suppression of 21 dBA.…”
Section: Electric Fields Applied To Thermoacoustic Instabilitiesmentioning
confidence: 99%
“…The ionization mechanism is primarily through chemical ionization and thus dependent on the fuel type and the fuel to air ratio. While this work only explored methane for the fuel, other fuels known to contain sizeable charge densities and be affected by electric fields include butane [30] , propane [30,35] , and acetylene. Application to other fuel types would require further study.…”
Section: Future Workmentioning
confidence: 99%
“…For example, Jocher et al 25 experimentally confirm that combustion instability could be controlled in open-loop configuration by applying a magnetic field via reducing the growth rate of flame perturbations. Henderson and Xu 26 experimentally study the effect of applying direct-current electric field on damping thermoacoustic instability in a horizontal Rijke tube. Approximately 20 dB SPL reduction is achieved.…”
mentioning
confidence: 99%